PROBLEMS OF WOMEN WORKERS IN COIR INDUSTRY IN KANNIYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Coir industry provides employment opportunities and generates income to the people particularly in rural areas and thereby promotes country’s economy. It is a labour -intensive industry which provides employment to more than 7,00,000 persons of whom majority are from rural areas belonging to the economically very weaker sections of the society. Nearly 80 percent of the workers are women in the fibre extraction and spinning sectors. India accounts for more than two-thirds of world production of coir and coir products. In India, 8 percent of the coir and coir products are exported to foreign countries and remaining 92 percent is domestically consumed.In this article the problems of women workers and their working condition are analysed and it was found out that no medical allowance and no job security are the major problems faced by women workers in coir industry.